In vitro viability of pollen grain of fiji dwarf coconut accession - Machado, Caroline de Araújo; Vendrame, Wagner Aparecido; Neto, Aurélio Rúbio; Chagas, Edvan Alves; Chagas, Pollyana Cardoso; Ledo, Ana da Silva (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2021)
Lethal Yellowing is a disease that causes severe damages to coconut palms and it has devastated the coconut canopy of several Caribbean islands, and areas of southern Florida. The Fiji dwarf coconut accession has demonstrated tolerance to lethal yellowing. Pollen storage and germination provides useful information for conservation strategy and genetic improvement programs. The objective of this experiment was to evaluate pollen viability of Fiji dwarf coconut by in vitro germination under different nutritional and abiotic conditions. For the first experiment, two liquid culture media were evaluated for in vitro germination of Fiji dwarf coconut pollen; the Lora culture medium and the Armendariz culture medium combined with four temperature levels. In the second experiment, different sucrose concentrations in the Lora culture medium (4, 8, 12 and 16%) were evaluated combined with two incubation times (6 and 24 hours) in the presence or absence of light. The highest in vitro germination of Fiji dwarf coconut pollen was obtained when pollen was inoculated in Lora culture medium at 28 ºC. The incubation time of 24 hours influence positively on the pollen tube protrusion. The light condition does not influence the germination process. The in vitro germination percentage improved as the sucrose concentration increased according to a linear regression and damage pollen grain percentage reduced as the sucrose concentration increased, according to a quadratic regression. Index terms: Cocos nucifera L.; in vitro germination; inflorescence; conservation.